The Cryptic African Wolf: Canis aureus lupaster Is Not a Golden Jackal and Is Not Endemic to Egypt - Rueness, Eli Knispel; Asmyhr, Maria Gulbrandsen; Sillero-Zubiri, Claudio; Macdonald, David W.; Bekele, Afework; Atickem, Anagaw; Stenseth, Nils Chr. (PLOS ONE, 2011)
The Egyptian jackal (Canis aureus lupaster) has hitherto been considered a large, rare subspecies of the golden jackal (C. aureus). It has maintained its taxonomical status to date, despite studies demonstrating morphological similarities to the grey wolf (C. lupus). We have analyzed 2055 bp of mitochondrial DNA from C. a. lupaster and investigated the similarity to C. aureus and C. lupus. Through phylogenetic comparison with all wild wolf-like canids (based on 726 bp of the Cytochrome b gene) we conclusively (100% bootstrap support) place the Egyptian jackal within the grey wolf species complex, together with the Holarctic wolf, the Indian wolf and the Himalayan wolf. Like the two latter taxa, C. a. lupaster seems to represent an ancient wolf lineage which most likely colonized Africa prior to the northern hemisphere radiation. We thus refer to C. a. lupaster as the African wolf. Furthermore, we have detected C. a. lupaster individuals at two localities in the Ethiopian highlands, extending the distribution by at least 2,500 km southeast. The only grey wolf species to inhabit the African continent is a cryptic species for which the conservation status urgently needs assessment.